Dampak Bank Keliling di Kampung Cikeyeup Desa Gunung Anten - Hasanah, Siti Badriyatul; Fadilah, Safira Qireina; Khasanah, Jaojatul; Meysaroh, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article aims to find out about the behavior of mobile bank borrowers and consider what problems the presence of these banks causes for the local community. This mobile bank is very popular among the lower middle class because it provides easy loan services and a fast process. This convenience makes mobile banks popular and accepted by the public as